(untitled) (Journal of the College of Basic Education, 2022)
In order to investigate the case of a change in antioxidants and some of biochemical changes in the serum of breast cancer patients by receiving chemotherapy and radiation therapy, it have been measure the level of anti-oxidants and the level of blood fat in the serum. The study included 60 female suffering from breast cancer They were treated at AL-Shifa Oncology Centre and Hospital, radiation and nuclear medicine in Misan province (treatment chemical therapy group(1) = 30 and a radiation therapy group(2) = 30) in addition to the 29 female from collage of medicine-Misan healthy represent the control group, for the period from October 2015 until February 2016. The level of MDA , was significant increase in the chemotherapy group (P ≤ 0.05) and it was significantly decreased in the radiotherapy group (P ≤0.001) compared with the control group. And the level of vitamin A, was significant increase in two groups of chemotherapy (P ≤ 0.05) and radiotherapy group (P ≤ 0.05) compared with the control group. The level of vitamin C, was significant increase in a chemotherapy (P ≤ 0.05) and radiotherapy group (P ≤ 0.05) compared with the control group. The level of cholesterol was significant increase in the chemotherapy group (P ≤ 0.05) and radiotherapy group (P ≤ 0.05) compared with the control group. And the level of triglycerides was significant decrease in the chemotherapy group (P ≤ 0.05) and radiotherapy group (P ≤ 0.05) compared with the control group.